Associations of urinary phthalate metabolites with Circadian Syndrome: evidence from NHANES - Chunxing Yi; Jie Shen; Jiansheng Cai (Frontiers in Public Health, 2025)
BackgroundThe relationship between phthalate exposure and circadian rhythm disruption lacks epidemiological evidence. This study investigated the association between exposure to ten phthalates (PAEs) and Circadian Syndrome (CircS) among American adults.MethodsData from the 2013–2018 United States National Health and Nutritional Health Surveys (N = 2519) were analyzed using logistic regression to assess associations between individual phthalate exposure and CircS. Restricted cubic splines (RCS) evaluated dose-response relationships, while Bayesian kernel machine regression (BKMR) and g-computation models assessed the effects of phthalate mixtures.ResultsThe prevalence of CircS in the study population was 45.14%. Participants in the fourth quartile of exposure to MECP phthalate (OR = 1.632, 95% CI: 1.159–2.300), MEHP phthalate (OR = 1.830, 95% CI: 1.301–2.573), mono-benzyl phthalate (OR = 1.699, 95% CI: 1.156–2.496), and MEOH phthalate (OR = 1.560, 95% CI: 1.065–2.279) had an increased risk of CircS compared to those in the first quartile of exposure. RCS analysis indicated a linear positive association between exposure to MECP, MEHP, and mono-benzyl phthalate and CircS risk. BKMR and quantile g-computation analyses demonstrated that combined phthalate exposure was positively associated with CircS.ConclusionIndividual and mixed exposures to certain phthalates may increase the risk of CircS, providing evidence for prevention strategies targeting endocrine-disrupting chemicals.